Preparation and shelf-life evaluation of Flaxseed incorporated biscuits - Rai, Vatsala; Acharya, Dev Raj (Himalayan Journal of Science and Technology, 2022)
Flaxseed incorporated biscuit is a baked, unleavened cake that uses flaxseed flour as the main component. The development of germinated flaxseed incorporated biscuit and the study of its storage stability were the main objectives of this study. Flaxseed was germinated up to 7 days at room temperature. Germination longer than 7 days resulted in significant mold growth. For this study, flaxseed flour was made from the 7- day germinated flaxseed. Five formulations were tasted in a laboratory setting using 0, 12.5, 25, 37.5, and 50 parts germinated flaxseed flour to wheat flour. Design Expert v13 software was utilized to formulate the recipe using D-optimal design. One way ANOVA without blocking was carried out at a 5% level of significance to measure consumer acceptability. According to mean sensory scores, a formulation containing 25 parts flaxseed flour was chosen for further analysis. Acid, peroxide, and moisture values were used to determine the shelf-life of the formulated biscuits. At the end of two months, the values obtained —0.21 mg KOH/g oil, 1.8 MeqO2/kg fat, and 4.88% were within the safer limits. Overall, flaxseed flour incorporation of 25 parts of flaxseed flour was successfully incorporated into the biscuit recipe. Calcium, iron, protein, ash, fiber, and fat were higher in the optimized product than the control.